1995
DOI: 10.3904/kjim.1995.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among 64k Autoantibodies, Pancreatic β-cell Function, HLA-DR Antigens and HLA DQ Genes in Patients with Insulin-Dependent Diabetes Mellitus in Korea

Abstract: ObjectivesAmong autoantibodies detected in patients with insulin-dependent diabetes mellitus(IDDM), antibodies to 64,000Mr islet protein(64k), now recognized as glutamic acid decarboxy lase(GAD), appear to be an even more predictive marker of IDDM than islet cytoplasmic antibody(ICA) or insulin autoantibody(IAA). We examined the relationships among 64k autoantibodies, pancreatic β-cell function, HLA-DR antigens and HLA-DQ genes in patients with IDDM in Korea.MethodsTo identify the 64k autoantibody, the immunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Our study showed that, despite comparable duration of diabetes, fasting C-peptide levels of rapid-onset Type 1 diabetic patients was significantly lower than those of slow-onset, which indicates the greater residual 13 cell mass of the latter. Clinical characteristics of adult patients with rapid-onset Type 1 diabetes in this study, except those of an older age at onset, are similar to those of childhood Type 1 diabetes reported elsewhere [4,9,10,21,22]. They had remarkably low fasting C-pep-378 tide levels, lean BMI and positive history of ketonuria or ketoacidosis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study showed that, despite comparable duration of diabetes, fasting C-peptide levels of rapid-onset Type 1 diabetic patients was significantly lower than those of slow-onset, which indicates the greater residual 13 cell mass of the latter. Clinical characteristics of adult patients with rapid-onset Type 1 diabetes in this study, except those of an older age at onset, are similar to those of childhood Type 1 diabetes reported elsewhere [4,9,10,21,22]. They had remarkably low fasting C-pep-378 tide levels, lean BMI and positive history of ketonuria or ketoacidosis.…”
Section: Discussionsupporting
confidence: 82%
“…Asian population is sparse [20][21][22]. Most studies were done in a mixed population of patients with childhood-and adultonset.…”
Section: Clinical Data Concerning Adult-onset Type I Diabetes In Thementioning
confidence: 99%
“…On the other hand, different structures of MHC molecules might affect antigen processing and presentation of GAD. There are only a few reports which address the question of how HLA antigens relate to GAD autoimmunity Lee et al, 1995]. Identification of a peptide sequence in GAD for T cell reactivity in human IDDM [Lohmann et al, 1994;Panina-Bordignon et al, 1995] and for prevention of IDDM in NOD mice [Tisch et al, 1993;Elliott et al, 1994;Gelber et al, 1994;Pleau et al, 1995] further substantiates the involvement of HLA molecules in GAD autoimmunity and the pathogenesis of IDDM.…”
mentioning
confidence: 98%
“…[8][9][10] There were only few studies concerning how HLA alleles relate to GAD autoimmunity. 11,12 In addition, some Asian population have shown rather low frequencies (5-50%) of GAD65 and ICA in T1D when compared with Caucasian recent onset T1D patients (63-84%). [13][14][15][16][17][18] GAD65Ab can be measured by radioimmunoassay.…”
Section: Introductionmentioning
confidence: 99%